Synthesis and biological evaluation of a novel class of curcumin analogs as anti-inflammatory agents for prevention and treatment of sepsis in mouse model - Zhao C; Zhang Y; Zou P; Wang J; He W; Shi D; Li H; Liang G; Yang S (Dove Medical Press, 2015)
Chengguang Zhao,1,2,* Yali Zhang,1,2,* Peng Zou,1 Jian Wang,3 Wenfei He,2 Dengjian Shi,2 Huameng Li,2 Guang Liang,2 Shulin Yang1 1School of Environmental and Biological Engineering, Nanjing University of Science and Technology, Nanjing, 2Chemical Biology Research Center, School of Pharmaceutical Sciences, 3Department of Orthopedics, The 1st Affiliated Hospital, Wenzhou Medical University, Wenzhou, People’s Republic of China *These authors contributed equally to this work Abstract: A novel class of asymmetric mono-carbonyl analogs of curcumin (AMACs) were synthesized and screened for anti-inflammatory activity. These analogs are chemically stable as characterized by UV absorption spectra. In vitro, compounds 3f, 3m, 4b, and 4d markedly inhibited lipopolysaccharide (LPS)-induced expression of pro-inflammatory cytokines tumor necrosis factor-α and interleukin-6 in a dose-dependent manner, with IC50 values in low micromolar range. In vivo, compound 3f demonstrated potent preventive and therapeutic effects on LPS-induced sepsis in mouse model. Compound 3f downregulated the phosphorylation of extracellular signal-regulated kinase (ERK)1/2 MAPK and suppressed IκBα degradation, which suggests that the possible anti-inflammatory mechanism of compound 3f may be through downregulating nuclear factor kappa binding (NF-κB) and ERK pathways. Also, we solved the crystal structure of compound 3e to confirm the asymmetrical structure. The quantitative structure–activity relationship analysis reveals that the electron-withdrawing substituents on aromatic ring of lead structures could improve activity. These active AMACs represent a new class of anti-inflammatory agents with improved stability, bioavailability, and potency compared to curcumin. Our results suggest that 3f may be further developed as a potential agent for prevention and treatment of sepsis or other inflammation-related diseases. Keywords: asymmetric mono-carbonyl analogs of curcumin (AMACs), stability, anti-inflammatory property, sepsis, QSAR